Helmholtz coils model as pulsed electromagnetic field therapy devices for fracture healing using comsol multiphysics. Issue 1 (January 2021) - Nismayanti, A; Jannah, H; Rugayya, S; Maskur,; Adawiyah, R
Abstract: The World Health Organization in 2009 recorded that more than a million people died due to accidents, and about 2 million people had physical accidents, namely fractures. The main challenge for clinicians today is finding an effective and inexpensive method of fracture healing. In this case, a pulsed electromagnetic field (PEMF) can be used, which is a non-invasive technique that is inductive and generates a magnetic field due to changes in the electric field. So this research aims to create a simulation design of PEMF therapy device for fracture healing. The stages of this research method are to make Helmholtz coil modelling of PEMF therapy device using Comsol Multiphysics with variations in the number of turns, the distance between two coils, voltage or current, and coil diameter, to obtain the correct magnetic field value to accelerate fracture healing. The result of this research is the successful design of a PEMF device that produces a magnetic field value B is 1.5 mT on the number of turns N is 150, the distance between two coils r is 2.5 cm, the current value I is 0.5 A, and coil diameter D is 5 cm.